Factor Influencing Customer Attitude towards Use Interest-free financial products and services of Commercial Banks in Ethiopia - Abdi Hassen Habib (HM Journals, 2021)
Islamic banking has become one of the global financial industries' fastestgrowing segments. This study analysis of Customer Attitudes towards the Use of Interest- Free Financial Products and Services of Commercial Banks in Ethiopia (The Case of Jigjiga City). 398 sample respondents were chosen from commercial banks in Ethiopia utilizing multistage staged sampling processes. Both of the original sources were used to gather the study's data. Interviews and structured questionnaires were used to gatherprimary data. The results of multiple regressions revealed that relative advantage and compatibility have a significant positive impact on the attitude toward interest-free banking products and services in commercial banks in Ethiopia. The data were used for descriptive analysis (frequency, percentile, mean, and standard deviation) as well as econometric analysis (correlation and multiple regressions). Similarly, complexity has no obvious influence on attitude, whereas perceived trust and customers awareness have a negative influence on attitude. .